2014
DOI: 10.1515/ijdhd-2014-0324
|View full text |Cite
|
Sign up to set email alerts
|

Development of a system for the assessment of a dual-task performance based on a motion-capture device

Abstract: The authors produced a dual task (DT) that provided a dynamic balance task and a cognitive task in a game system using motion sensors and virtual images. There had been no DT where a cognitive task needs a dynamic balance task that requires full-body motions. We developed and evaluated a game system to assess the performance of the DT. The DT was to solve a Sudoku puzzle using full-body motions like Tái Chi. An ability to perform a DT is intimately related to risk of falls. To evaluate the developed system, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The DTTC test [ 8 - 10 ] requires users to solve a number placement problem (Sudoku) by controlling a stick figure with the movement of their entire body. The user’s full-body motion is captured using Kinect and is translated into movements for the stick figure on a screen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DTTC test [ 8 - 10 ] requires users to solve a number placement problem (Sudoku) by controlling a stick figure with the movement of their entire body. The user’s full-body motion is captured using Kinect and is translated into movements for the stick figure on a screen.…”
Section: Methodsmentioning
confidence: 99%
“…With a focus on DT, we developed a new concept called the Dual-Task Tai Chi (DTTC) test [ 8 ]. This system was developed using Kinect (Microsoft, Redmond, WA, USA), a motion-capture device, and demonstrated that the DTTC test quantitatively evaluates compound functions, including DT, balance, and cognitive abilities in elderly people [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DTTC test [8][9][10] requires users to solve a number placement problem (Sudoku) by controlling a stick figure with the movement of their entire body. The user's full-body motion is captured using Kinect and is translated into movements for the stick figure on a screen.…”
Section: B Devicementioning
confidence: 99%
“…A pilot experiment indicated that the test-retest reliability for completion time was considerably high (inter-trial correlation coefficient, 0.94; 95% confidence interval, 0.86-0.97; P < 0.001). 14…”
Section: Measurement Devicementioning
confidence: 99%
“…We developed a new concept device to assess DT ability and named it the ''Dual-Task Tai Chi'' (DTTC) test. 14 To quantify DT skill, we developed this system using Kinect, a motion-capture device. We chose Tai Chi as a locomotive task and Sudoku as a cognitive task.…”
Section: Introductionmentioning
confidence: 99%